Location of mea-1 in LG IL of Neurospora crassa - C. H. Wilson (Fungal Genetics Reports, 1990)
mea-1 (methyl ammonium resistant) confers resistance to 50 mM methylamine in nitrate medium. It maps in the vicinity of acr-3in IL, as indicated in a cross of un-16 acr-3 x mea-1. Scoring was done with 103 un+ spores.